2018
DOI: 10.1021/acs.energyfuels.7b04055
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Capture by Kaolin, Part 2: K2CO3, KCl, and K2SO4

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 57 publications
(158 reference statements)
2
40
0
Order By: Relevance
“…The median diameter (D ) of ASV2CFA0-32, ASV2CFA32-45 and ASV2CFAGR was 10.20 μm, 33.70 μm and 6.03 μm, respectively. The D 50 of ASV2CFAGR is comparable with that of kaolin (5.47 μm) and mullite (5.90 μm) utilized in our previous studies [32,33]. A sieving analysis showed that ASV2CFA0-32 contributed 63.0 wt.…”
Section: Methodssupporting
confidence: 75%
“…The median diameter (D ) of ASV2CFA0-32, ASV2CFA32-45 and ASV2CFAGR was 10.20 μm, 33.70 μm and 6.03 μm, respectively. The D 50 of ASV2CFAGR is comparable with that of kaolin (5.47 μm) and mullite (5.90 μm) utilized in our previous studies [32,33]. A sieving analysis showed that ASV2CFA0-32 contributed 63.0 wt.…”
Section: Methodssupporting
confidence: 75%
“…Consequently, the dehydroxylation data of 800 • C and 1300 • C were not involved in the kinetic analysis. There were 34 mechanism functions used for the primary linear fitting of the dehydroxylation data of 900-1200 • C according to Equation (8) [4,24,25]. The highest linear correlation coefficient was from the random nucleation and subsequent growth model of f (α 4 ).…”
Section: Kaolinite Dehydroxylation Kineticsmentioning
confidence: 99%
“…During combustion, gasification and other processes, these semi-volatile metals are prone to cause the problems such as boiler slagging, ash deposition of heat transfer area, high-temperature corrosion, and emissions of heavy metals and ultra-fine particles [1][2][3][4][5]. Kaolinite can adsorb alkali/heavy metal vapor at high temperatures, and then be captured by dust removal equipment [6][7][8]. Therefore, the problems mentioned above can be solved by kaolinite addition into the furnace.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have indicated that the main source of element K in heating surface deposits is gas phase K in biomass combustion [4,5,[8][9][10]. In this study, with the condition of combustion temperature (800 °C) and low Cl content in fuel, K probably enters the gas phase mainly in the form of KOH in place of KCl and K2SO4.…”
Section: Migration and Deposition Of Alkali Metalmentioning
confidence: 77%
“…The dominant elements in biomass ash are Ca, K, Cl and S [2,3]. During combustion, K element in biomass fuel is released to the gas phase in the form of KCl, KOH and K 2 SO 4 [4][5][6][7][8][9][10]. These potassium-containing compounds cause severe slagging due to their low melting temperature [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%